Drug-coated balloon therapy is more effective in treating late drug-eluting stent in-stent restenosis than the early occurring one—a systematic review and meta-analysis - Kulyassa, Péter; Engh, Marie Anne; Vámosi, Péter; Fehérvári, Péter; Hegyi, Péter; Merkely, Béla; Édes, István Ferenc (Frontiers in Cardiovascular Medicine, 2023)
Drug-eluting stent in-stent restenosis (DES-ISR) remains one of the important assignments to be resolved in interventional cardiology, as it is present in 5%–10% of total percutaneous coronary intervention cases. Drug-coated balloon (DCB) utilization is promising, as it comes with long-term protection from recurrent restenosis in optimal conditions without the hazard of higher risk for stent thrombosis and in-stent restenosis. We aim to reduce the need for recurrent revascularization in DES-ISR, specifying the population in which the DCB therapy should be used. In this meta-analysis, the results of studies containing data on the time frame between drug-eluting stent implantation and the clinical presentation of in-stent restenosis and concomitant drug-coated balloon treatment were summarized. A systematic search was performed in Medline, Central, Web of Science, Scopus and Embase databases on November 11th, 2021. The QUIPS tool was used to assess the risk of bias in the included studies. The occurrence of a major cardiac adverse events (MACE) composite endpoint, containing target lesion revascularization (TLR), myocardial infarction, and cardiac death, and each of these separately, was assessed at 12 months after the balloon treatment. Random effects meta-analysis models were used for statistical analysis. Data of 882 patients from four studies were analyzed. Across the included studies, a 1.68 OR (CI 1.57–1.80, p < 0.01) for MACE and a 1.69 OR (CI 1.18–2.42 p < 0.01) for TLR were observed, both in favor of late DES-ISR. The main limitation of the study is the relatively low patient number. Nevertheless, this analysis shows the first statistically significant results for the effect of DCB treatment in the early or late presentation of DES-ISR. As to date, intravascular imaging (IVI) remains limitedly accessible, other landmarks as the time frame of in-stent restenosis development are to be pursued to advance therapeutic outcomes. In consideration of other biological, technical and mechanical factors, time frame of occurrence as a prognostic factor could reduce the burden of recurrent revascularization in patients at an already high risk. Systematic Review Registration: identifier [CRD42021286262].